le rolle de la Banque mondiale. (Washington, 2005)
This book takes an in-depth look at health, nutrition, and population (HNP) challenges faced by Sub-Saharan Africa, particularly how disease, malnutrition, and high fertility affect poverty reduction
Keywords: Social aspect